Konsep Syukur Perspektif Ibnu Athaillah (Studi Analisis dalam Kitab al-Hikam) - Sahila Nurahmah Lutviani (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to discuss the concept of Ibn Atha'illah's gratitude. This study uses a qualitative approach with descriptive analysis method. The formal object in this study is Ibn Atha'illah's thoughts regarding gratitude. While the material object in this study is the concept of gratitude. The data used in this study are primary and secondary data. The primary data used is the book of Al-Hikam which was written directly by Ibn Atha'illah, while the secondary data used are journals, books, documents and so on related to the object being studied. The results of this study are that gratitude is a part of the station formulated by Ibn Atha'illah which is addressed to someone who wants to reach Allah SWT. The conclusion in this study is that gratitude according to Ibn Atha'illah is divided into three parts, namely oral, heart, and body parts.